Modernization of public management in regional governments, a literary review - Chávez-Rivas, Patricia Ivonne (2024)
This review article aims to identify the main tools for modernizing public management at different levels of government. The method used corresponds to an inquiry and selection of scientific articles, referring to the modernization of public administration at different levels. of government. A review of 40 articles indexed in different databases was carried out, such as EBSCO, web of science Scopus, Scielo and Latindex. These investigations were carefully selected taking into account certain criteria such as: the year of publication, which must be a maximum of 4 years old, from 2018 to this year; subject area; idiom; among others. This study reached the main results. The main challenges of public management are: a culture focused on the citizen; vocation to service on the part of public servants, management of information and communication technologies, access to innovative mechanisms This review article concludes that the most important tools for modernizing public management are: management by results, management by objectives, open government, e-government and the management of organizational culture and values.